INDUCTION PROGRAMME: AN ESSENTIAL INGREDIENT FOR STAFF DEVELOPMENT AND QUALITY TEACHER OUTPUT IN BASIC EDUCATION IN NIGERIA - Ndayelechi, Abubakar (Sokoto Educational Review, 2014)
This paper identified the challenges of teachers and that of teaching profession they include: inadequate training, poor condition of service and lack of professionalism. It also looked at induction programme for the beginning teachers, with particular reference to mentoring as a very important model for making quality teachers. The paper made some recommendations, these include: research and experimentation based institutions also serving as centres of innovations, Colleges of Education to be in close ties with societies, revival of Teachers Colleges, in-services training, improvement on criteria for recruitment into training colleges, thorough training in academic subjects and need for continuous assessment of the teacher-trainee and teachers on the job. These recommendations will hopefully bring about the much-needed quality teachers if put into use or implemented.